Handbook of Florists' Crops Diseases (Handbook of Plant Disease Management,, 2018)
Chapters outline up-to-date strategies regarding breeding, chemical and biological control, cultural and environmental manipulation, diagnosis, nutrition, and sanitation and how these approaches directly influence ornamental plant health. This book is a presentation of the latest techniques for disease management by a global team of experts. The book addresses the major diseases of economically important ornamentals with the goal of capturing the latest disease management strategies along with diagnostic photographs. Florists' crops production has evolved considerably through new technological advances in irrigation, environmental control, along with the appearance of new centers of large scale production of plant material. These changes have necessitated the development of newer and innovative ways of suppressing pathogenic fungi, bacteria, viruses, and nematodes. .